2013
DOI: 10.1177/2150135113497767
|View full text |Cite
|
Sign up to set email alerts
|

Innominate Artery Cannulation and Antegrade Cerebral Perfusion for Aortic Arch Reconstruction in Infants and Children

Abstract: Innominate artery cannulation is a safe and effective technique for aortic arch reconstruction in nonneonates. We conclude that antegrade cerebral perfusion is a useful technique for aortic arch reconstruction in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The innominate artery has increased in popularity as a cannulation site [7] [8]. The safety and efficacy of innominate artery cannulation was demonstrated by Nasirov et al in a retrospective review of 42 pediatric patients undergoing aortic arch surgery [1]. There were no operative mortalities or evidence of clinical neurologic injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The innominate artery has increased in popularity as a cannulation site [7] [8]. The safety and efficacy of innominate artery cannulation was demonstrated by Nasirov et al in a retrospective review of 42 pediatric patients undergoing aortic arch surgery [1]. There were no operative mortalities or evidence of clinical neurologic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Innominate artery cannulation provides a safe and easily reproducible alternative and prevents many of the disadvantages seen in femoral and axillary artery cannulation. Its use in pediatric cardiac surgery has seen a rise [1]. Herein, we describe the technique for innominate artery cannulation in pediatric patients undergoing redo sternotomy and review our experience with the technique.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cited literature varies widely in range for ACP from 10 to 100 mL/kg/min, studies utilizing NIRS technology or visual light spectroscopy have indicated that ACP flow rates of greater than 30 mL/kg/min are sufficient to maintain adequate cerebral and somatic oxygen saturations (12,19,40). Admittedly, these findings must be evaluated within the context of temperature and blood gas management (pH versus alpha stat) among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…In newborns and infants, extended end-to-end repair of coarctation is performed routinely at near-normothermia with all cerebral and systemic perfusion achieved via the innominate artery for periods of approximately 20 minutes, without clinically significant neurological or end-organ injury (17). Notwithstanding, few reports evaluate the use of moderate hypothermia for ACP in neonates and children undergoing aortic arch reconstructions (11,12,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…7 A number of techniques have been described for selective antegrade cerebral perfusion. 3,4,8,9 Indirect cannulation involves anastomosing a length of tube graft to the innominate artery, but this increases the complexity of the operation, may cause continuous blood loss from the anastomosis, and possibly provides poorer flow rates. Others have used direct distal ascending aortic cannulation, advancing the cannula into the innominate artery while the anastomosis is performed, but this risks damage to the intima of the innominate artery and is obtrusive when performing a delicate aortic anastomosis in a small neonate.…”
Section: Introductionmentioning
confidence: 99%